Techno-Legal Implications Of Privacy - Min, Chee Fee (2002)
The focus of this thesis is to provide an understanding of the privacy issues on the Internet. Threats to privacy on the Internet have always been a barrier to the success implementation of e-commerce. Public stay off the Internet because they do not want